PENGARUH LATIHAN PLYOMETRIC TERHADAP HASIL TENDANGAN BOLA LAMBUNG JAUH PADA PEMAIN SEPAKBOLA PORDA PUTRI KUNINGAN - Adila, Widi Gusti; Astria Nur, Hana (Journal of Physical Education and Sport Science, 2025)
Widi Gusti Adila(NIM:182223145),The Effect of Plyometric Exercises on the Results of Long Stomach Ball Kicks in Porda Putri Kuningan Soccer Players, Physical Health and Recreational Education (PJKR),2022 The ability to kick long balls must be possessed by porda brass soccer players using plyometric exercises.Plyometrics is an exercise method to increase the strength and power of certain muscles. This researcher aims to find out how much influence plyometric exercises have on the results of long stomach ball kicks. The research approach uses a quantitative approach and experimental methods. The subjects in this study were women's brass soccer players.Data were collected through(post-test) and(pre-test)